Analysis of Hybrid Electric Vehicle Technologies - Keldiyarova Malika Shukhrat qizi (Research Parks Publishers, 2021)
Demands for more efficient vehicles with reduced fuel consumption and low emissions are growing rapidly in these days. Generally, they can create a competition among automakers in the worldwide. In order to satisfy these kind of factors, using of hybrid electrical powertrains in vehicles can be regarded one of the solution. In this study, the background theories on different types of Hybrid Electrical vehicles (HEVs) are described precisely. The main purpose of this article to analyze advantages and disadvantages of every technologies and to research their efficiency.